2018
DOI: 10.1016/j.buildenv.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessing visitors' thermal comfort in historic museum buildings: Results from a Post-Occupancy Evaluation on a case study

Abstract: Adaptive reuse of historic buildings as museums is an effective strategy for retaining heritage architectures while achieving environmental sustainability objectives.Building adaptation, retrofitting and preserving optimal environments for artwork and exhibit preservation are inherently complex, multifaceted tasks. However, indoor microclimates do not only affect collections; occupants and visitors must also be considered. The aim of this research is to explore whether artwork preservation constraints in reuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 39 publications
3
18
0
2
Order By: Relevance
“…These findings could shed light on the findings in previous field studies of spatial transition from outdoors to indoors [ [33], [34], [35], [36]]. They generally found that occupant (visitors) who just arrived the buildings tended to feel warmer than those who stayed longer.…”
Section: Discussionsupporting
confidence: 70%
“…These findings could shed light on the findings in previous field studies of spatial transition from outdoors to indoors [ [33], [34], [35], [36]]. They generally found that occupant (visitors) who just arrived the buildings tended to feel warmer than those who stayed longer.…”
Section: Discussionsupporting
confidence: 70%
“…The survey was prepared following standards ISO 10551 [57]. Several studies adopt the subjecting approach by submitting surveys [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. Sometimes, particular conditions or particular users, such as children in a 4-5 years age range [15,63], require the survey to be integrated or adapted to facilitate the understanding and the filling procedure.…”
Section: Subjective Approach: Thermal Comfort Surveymentioning
confidence: 99%
“…The authors suggested installing exhaust fans which have a potential of reducing the percentage of dissatisfied people by 87-91%. Martinez-Molina et al [18] assessed visitors' thermal comfort in historic museum buildings. The results show that the PMV model predicts the visitors' thermal comfort to be cooler than actual.…”
Section: Introductionmentioning
confidence: 99%